PENGEMBANGAN LKS PRAKTIKUM INSEKTA KELAS X SMA - RATRI BAKTI HARIATI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
The objective of this research were to develop Practice Worksheets of Insects as well as describe theoretical and empirical feasibility of this worksheets. This practice worksheets was developed by using 4-D models (without disseminate stage). The results indicated that Practice Worksheets of Insects was feasible (percentage 81.25%). The trial of implementation in the school indicated the majority of students gave positive response to Practice Worksheets of Insects, namely 88%. Keywords: practice worksheets, insect, first grade of senior high school